(untitled) (Baghdad Science Journal, 2025)
In this work, we are obviously interested in a general solution for the calculation of the image of a single bar in partially coherent illumination. The solution is based on the theory of Hopkins for the formation of images in optical instruments in which it was shown that for all practical cases, the illumination of the object may be considered as due to a self – luminous source placed at the exit pupil of the condenser , and the diffraction integral describing the intensity distribution in the image of a single bar – as an object with half – width (U0 = 8 ) and circular aperture geometry is viewed , which by suitable choice of the coherence parameters (S=0.25,1.0.4.0) can be fitted to the observed distribution in various types of microscope , the aberration were restricted to defocusing and coma upto third – order , the method of integration was Gauss quadrature: The necessary set of integration depends , of course , on the amount of present aberrations and had to be chosen (20) points of Gauss which decrease the computation time to few seconds: The aberration free systems corresponding to the paraxial receiving plane (W20= 0.0) is especially interesting as it predicts diffraction pattern shape. The influence of defocusing is very pronounced and relatively distorts the object , the influence of the off – axis aberration (third – order coma ), in which it was shown that for the high peaks in the images are most noticeable in the region of almost perfect coherence (S=0.25). As (S) is increased from (0.25) to (1.0) there is a pronounced redistribution of intensity, with peaks moving from one side of the image to the other. Calculations were also performed for systems having spherical aberration, but the results are qualitatively similar to an aberration – free defocused system and are omitted, so we will not present any numerical results. A computer program was written in FORTRAN 77 which solved the modified intensity distribution of Hopkins for(U´) dimensionless distance. The advantage of that additional work on this class of problems to investigate the development of more efficient numerical methods, also the reduction in computation time to few seconds for data runs for individual curves of intensity.